2000
DOI: 10.1037/1089-2699.4.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications of groups: From Pratt's "thought control classes" to modern group psychotherapy.

Abstract: longer accurate to define therapy as something that happens in only inpatient or clinical settings. It now covers a much wider range of applications than first occurred when Dr. Pratt treated tuberculosis patients in a group or class format in 1905. A more complete review of this history can be found in Fuhriman and Burlingame (1994). Generally, group therapy is used to treat existing problems from psychopathology (e.g., depression) to problems in living (e.g., parents dealing with teenagers), ranges in durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 65 publications
0
43
0
3
Order By: Relevance
“…Since all the reviewed studies used group-based cooking interventions, it is unclear from the studies whether the benefits found were related to the act of learning to cook or to the act of learning to cook with others . Group interaction has been used as a therapeutic modality in psychotherapy for more than 100 years (Barlow, Burlingame, & Fuhriman, 2000), and other experience-based group activities in therapeutic settings have been shown to have similar psychosocial effects (Catlin, Milliorn, & Milliorn, 1992). While two studies incorporated waitlist control groups, none added an interactive control group participating in another type of group activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since all the reviewed studies used group-based cooking interventions, it is unclear from the studies whether the benefits found were related to the act of learning to cook or to the act of learning to cook with others . Group interaction has been used as a therapeutic modality in psychotherapy for more than 100 years (Barlow, Burlingame, & Fuhriman, 2000), and other experience-based group activities in therapeutic settings have been shown to have similar psychosocial effects (Catlin, Milliorn, & Milliorn, 1992). While two studies incorporated waitlist control groups, none added an interactive control group participating in another type of group activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, it adds to group process studies with children. There is a lack of literature on the effect of group process with children's groups (Barlow, Burlingame, & Fuhriman, 2000;Webster-Stratton & Herman, 2008), especially studies linking group interventions and academic achievement (Brigman & Webb, 2007). Second, this adds to prevention literature by examining the effects of small-group preventive interventions in a bilingual setting, and reinforces the need to devote more attention to skills training models as a means of reducing academic failure (Bacallao & Smokowski, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…Despite cautions about the potential for harm in groups (Galinsky & Schopler, 1977;Roback, 2000), there is evidence that "groups work" (Barlow, Burlingame, & Fuhriman, 2000;Burlingame, Fuhriman, & Mosier, 2003;Hoag & Burlingame, 1997). Group work benefits individuals across the life span (Bratton, Ray, Rhine, & Jones, 2005;Hoag & Burlingame, 1997;Page, Weiss, & Lietaer, 2001;Weisz, Weiss, Han, Granger, & Morton, 1995), including children and adolescents (Cramer-Azima, 2002).…”
Section: Downloaded By [Northeastern University] At 07:33 03 Decembermentioning
confidence: 96%